Active externalism, virtue reliabilism and scientific knowledge. - Palermos, Spyridon (Synthese, 2015)
Combining active externalism in the form of the extended and distributed cognition hypotheses with virtue reliabilism can provide the long sought after link between mainstream epistemology and philosophy of science. Specifically, by reading virtue reliabilism along the lines suggested by the hypothesis of extended cognition, we can account for scientific knowledge produced on the basis of both hardware and software scientific artifacts (i.e., scientific instruments and theories). Additionally, by bringing the distributed cognition hypothesis within the picture, we can introduce the notion of epistemic group agents, in order to further account for collective knowledge produced on the basis of scientific research teams.